Peer effects, cooperation and competition in human capital formation (2012)
Economic literature has identified positive effects of peer abilities on individual achievement. However, the intuitive arguments supporting this evidence are not clear. This article presents a specific mechanism: cooperation and competition among group members; more precisely, the presence of positive and negative externalities in human capital accumulation. First, I develop an economic model that incorporates both kinds of externalities and shows the existence of an optimal level of competition between group members that maximizes human capital accumulation. Then, using data from PISA (2000) and an empirical strategy that controls for potential endogeneity issues, I find empirical evidence supporting the main results of the theoretical model. Namely, I find robust evidence of a non-linear effect of competition on academic performance. These results are consistent with the proposed model and the presence of positive technological externalities in educational production functions.